Volume 1: 20th Computers and Information in Engineering Conference 2000
DOI: 10.1115/detc2000/cie-14620
|View full text |Cite
|
Sign up to set email alerts
|

Extending Express-G to Model Fuzzy Information in Product Data Model

Abstract: Information with uncertainty and imprecision is inherently presented in engineering design and manufacturing. The nature of uncertainty and imprecision is incompleteness. The incompleteness is a typical feature in earlier product design phases. Product design is essentially viewed as a process of reducing the incompleteness in the description of conceptual design. Some methods and strategies for the preliminary engineering design, calculation, and modeling in relational database systems have been proposed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research on shopping tourism is also limited in that it is distributed highly unequally; in 2016, Choi et al found that 70% of research on shopping tourism to date has focused on the USA and East and Southeast Asia. In tourism research on Hainan, researchers have concentrated on tourism resource development (Ma et al, 2018; Shen & Tian, 2010), tourism management (H. Dong et al, 2019; W.…”
Section: Introductionmentioning
confidence: 99%
“…Research on shopping tourism is also limited in that it is distributed highly unequally; in 2016, Choi et al found that 70% of research on shopping tourism to date has focused on the USA and East and Southeast Asia. In tourism research on Hainan, researchers have concentrated on tourism resource development (Ma et al, 2018; Shen & Tian, 2010), tourism management (H. Dong et al, 2019; W.…”
Section: Introductionmentioning
confidence: 99%